Computer Modelling of Platelet Aggregation to Improve Their Cold Storage Methods - Zabielina, Daria S.; Mysochka, Anastasia Ye.; Utytskykh, Tetiana O. (Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2019; 29(2): 162.